2011
DOI: 10.3109/09286586.2011.590918
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up Survey of Cataract Surgical Coverage and Barriers to Cataract Surgery at Nkhoma, Malawi

Abstract: Our results demonstrate a 5-fold increase in coverage in the 6 years, primarily by increasing efficiency of the service provider and providing a community screening and referral service. Supporting the ophthalmic personnel with appropriate infrastructure and management has been central to this shift. Implementing an active case finding and referral mechanism has enabled this unit to provide regular high volume cataract surgery. There is a need to understand the factors influencing perceptions about cost as a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
(16 reference statements)
0
12
1
Order By: Relevance
“…Yorston 26 highlighted four major obstacles that deter people from receiving cataract surgery in developing countries, each of which has been validated independently in a variety of settings: Lack of knowledge, 14,15,21 perception of poor surgical quality, 11,13,14 transportation, 12,15,16,21 and cost. 10,11,18,19 The major barrier for poor uptake of low-cost cataract surgery in our study was lack of family support, which is similar to earlier reports from other countries, 11,27 but differs from previous reports from China, 14,17,22 Recent reports from China showed that lack of knowledge about cataract, concerns about the quality of local services, 14,17 and cost 19,22 appeared to be the principal barriers. One possible explanation for this apparent discrepancy is that we mainly focused on a specific population who had already been provided with an option of low-cost surgery as well as a detailed explanation of the surgical procedure.…”
Section: Other Reasonscontrasting
confidence: 53%
See 1 more Smart Citation
“…Yorston 26 highlighted four major obstacles that deter people from receiving cataract surgery in developing countries, each of which has been validated independently in a variety of settings: Lack of knowledge, 14,15,21 perception of poor surgical quality, 11,13,14 transportation, 12,15,16,21 and cost. 10,11,18,19 The major barrier for poor uptake of low-cost cataract surgery in our study was lack of family support, which is similar to earlier reports from other countries, 11,27 but differs from previous reports from China, 14,17,22 Recent reports from China showed that lack of knowledge about cataract, concerns about the quality of local services, 14,17 and cost 19,22 appeared to be the principal barriers. One possible explanation for this apparent discrepancy is that we mainly focused on a specific population who had already been provided with an option of low-cost surgery as well as a detailed explanation of the surgical procedure.…”
Section: Other Reasonscontrasting
confidence: 53%
“…Barriers to uptake of cataract surgery have been well-described in Africa 6,[9][10][11] and Asia, [12][13][14][15][16][17] and appear to include direct and indirect costs, 10,11,18,19 lack of knowledge, 13,20 fear of surgery, 13,20 concerns about the quality of services, 11,13 transportation problems, 12,15,16,21 and discrimination on the basis of sex and age. 12,15,16 Information on barriers to cataract surgery in China is sparse; barriers 14,17,19,22 include lack of knowledge, concern over poor quality of local services and cost of cataract surgery.…”
Section: Introductionmentioning
confidence: 96%
“…Using SICS in this population, an initial post-operative rise in IOP resolves by approximately 48 h [19]. Highvolume SICS has been instrumental for a fivefold increase in the cataract surgical coverage within a 10 mile radius of Nkhoma in 6 years [20].…”
Section: Discussionmentioning
confidence: 99%
“…First, performing serial cross-sectional population-based surveys to demonstrate evidence of a reduction in prevalence of cataract (and blindness and VI due to cataract) over time 14 34. Another indicator is to measure the CSC which represents a ratio of the met and unmet need for cataract surgery and is a measurement of the capability of a healthcare system to provide cataract surgical services to the population 35.…”
Section: Discussionmentioning
confidence: 99%